Online Expert System for forming Project Team - Ismail, Nurul Amira (Universiti Teknologi Petronas, 2006)
This report was about the research on how the information and communication technologies (ICT) and the development of tools can help students in higher education [earn through communication and collaboration with other learners. The objective of the study was to assist IT/IS students in forming a project team according to their roles and sroficiency based on their interest in order to match students ability with the skills needed n a project team. This report provides some theories which are related to the set of skills md guidelines on how to build a project team as well as other requirements in forming a :eam. By providing example of relevant subjects, it helps to create better view in onderstanding project team needs. Other than that, this report also includes a sample of nerely similar project done by other university but with different approach. These findings can be adapted in the implementation phase ofthis project. \n online expert system such as this particular system is the alternative method in lelping students to form a better project team. All of these findings were found through inline research, decision support system book as well as from the information resource ;enter. The results and discussion shows the effectiveness of both methods which are the ;onventional system and the online expert system. In conclusion, identifying students' ;apabilities and interest is important so that the selection of team members can be done smoothly and accurately. However, without a well-defined set of skills for each team nember's roles, the selection may be difficult and the results may not be as encouraging is people always expected a project team to be. Best selection of team members makes ?est productivity from the team as well. Furthermore with the combination of other ;lements such as responsibility, commitment, proficiency and so on will help in gaining ;eam trust and lead towards team effectiveness. in